Gastroparesis as a complication in the patient with traumatic brain injury - Sandra Marcela Mass-Ramirez (Romanian Neurosurgery, 2021)
Patients with acute neurological diseases (traumatic brain injury, hemorrhagic or ischemic stroke, spinal cord injury or tumour) may present with various systemic alterations such as changes in cardiovascular and respiratory response, gastrointestinal function disorders, metabolic and endocrinological abnormalities, coagulopathies, among others. Head injury increases the risk of malnutrition due to multiple factors related to nutrient intake, abnormalities in energy expenditure, eating behaviour disorders, gastrointestinal changes, and medication side effects. Gastrointestinal conditions include gastroparesis, which is defined as a delay in gastric emptying in the absence of mechanical obstruction. These patients often report nausea, vomiting, pain, postprandial fullness and abdominal swelling. Although the exact mechanism by which it occurs in traumatic brain injury is not known, it is related to complications such as intracranial hypertension, so it is most often seen in cases of severe trauma. Therefore, the objective of this review is to expose basic and practical concepts about gastroparesis and its approach.